Influence of endoscopic sinus surgery on the quality of life of patients with early nasopharyngeal carcinoma and the analysis of prognosis-related factors - Yong-Feng Si; Gui-Ping Lan; Zhuo-Xia Deng; Jing-Jin Weng; Jin-Yuan Si; Yang-Da Qin; Bo Huang; Yong-Li Wang; Yong Yang; Yin Qin; Ben-Jian Zhang; Xing Han; et al. (Tumor Biology)
The aim of this study is investigate the influence of endoscopic sinus surgery on the quality of life and prognosis of patients with early nasopharyngeal carcinoma. Patients initially diagnosed with early nasopharyngeal carcinoma and received surgical treatment were matched with nasopharyngeal carcinoma patients who received chemoradiotherapy at a ratio of 1:1, according to the following seven factors: gender, age, T staging, N staging, clinical staging, radiotherapy options, and chemotherapy options. Patients in the surgery group received endoscopic sinus surgery plus chemoradiotherapy, while subjects in the control group received chemoradiotherapy. The quality of life of patients before and after treatment was evaluated based on the FACT-H&N (Functional Assessment of Cancer Therapy-Head and Neck) and QLQ-H&N35 (Head and Neck Cancer Specific Module) questionnaires. In addition, overall survival and disease-free survival were compared between these two groups. The results showed overall survival was superior in the surgery group compared with the control group ( p = 0.007). However, the difference in disease-free survival between these two groups was not statistically significant ( p = 0.128). Furthermore, subgroup analysis revealed that for N0 patients, the effect of surgery combined with chemoradiotherapy on overall survival was superior to that of chemoradiotherapy ( p = 0.048); while for N1 patients, the difference in overall survival between these two groups was not statistically significant ( p = 0.065). For early nasopharyngeal carcinoma patients without lymph node metastasis, overall survival and disease-free survival in T1 patients were superior to those in T2 patients (χ 2 = 4.403, p = 0.036; χ 2 = 4.542, p = 0.033). At the end of treatment, the pain score was found to be significantly lower in the surgery group than in the chemoradiotherapy group ( p = 0.027). At 3 months and 1 year after treatment, dry mouth scores were significantly lower in the surgery group than in the chemoradiotherapy group ( p = 0.002, p = 0.026). These results demonstrated that the curative effect of surgery combined with chemoradiotherapy in the treatment of nasopharyngeal carcinoma was satisfactory and was particularly suitable for N0 patients.